BTI - 2022 Togo Country Report : political and socio-economic development, 2019-2020 [enhanced author's version] - Kohnert, Dirk (My University, 2020)
The Gnassingbé clan has ruled the country since 1967. The demand for political alternance, constituted the major contentious issue between the government and the challengers of the Gnassingbé regime throughout the survey period. The first local elections since more than 30 years took finally place on 30 June 2019and resulted in the victory of the ruling party. Shortly afterwards, in February 2020, the President won also the disputed presidential elections and thus consolidated his power, assisted by the loyal army and security services. The outbreak of the Corona epidemic in Togo in April 2020 and the subsequent economic recession may have contributed to limit popular protest against the Gnassingbé regime. The human rights record of the government has improved but remains poor. Despite undeniable improvements to the framework and appearance of the regime's key institutions during the review period, democracy remains far from complete. However, the international community, notably Togo’s African peers, the AU and ECOWAS, followed a ‘laissez-faire’ approach in the interests of regional stability and their national interests in dealing with Togo. Economic growth remained stable at about 5% per annum (before Corona). Public investment in infrastructure and increases in agricultural productivity, notably of export crops, had been the key drivers of economic growth. However, growth remains vulnerable to external shocks and the climate and has not been inclusive. Moreover, it was overshadowed by increasing inter-personal and regional inequality as well as an increase in extreme poverty. Money-laundering, illegal money transfers and trafficking grew alarmingly. Nevertheless, the business climate improved considerably
Keywords: democratization; governance; fragile states; political and socio-economic development; development co-operation; EU; Togo; West Africa; ECOWAS